The influence of social background on learning a foreign language - Siladi Vasyl; Szilágyi László; Сіладі Василь (Skleněný Můstek-MCNlP, 2019)
Abstract. School can play an important role in the formation, conservation or mitigation of social differences among students. The school is the institution where these social differences are best observed and measured. [3] Nowadays, the increase in differences between students is rising, and the reason for this trend is strong school selection. Nowadays, parents and their children can choose the right one from a multitude of schools, and this increases the proportion of pupils in so-called 'elite' schools, while others can attend less quality education.
Keywords: motivation; language strategy; education; condition; knowledge; curriculum; development; success; support